Particle size of corn in lactation diets for mixed-parity sows - Baudon, E.C.; Hancock, Joe D.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 107 mixed-parity sows (parities one to four) was used to determine the effects of particle size of corn in lactation diets on sow and litter performance. The sows were fed corn-soybean meal-based diets with targeted corn particle sizes of 1,500, 900, and 600 μm (actual means particle sizes of corn during the experiment were 1,600, 824 and 619 μm). Reducing mean particle size of the corn in lactation diets from 1,500 to 600 microns resulted in greater ADFI and water usage (linear effects, P<0.02), fewer days for return to estrus after weaning (linear effect, P<0.04), and less backfat loss (quadratic effect, P<0.03) for the sows. Although the trends in pigs weaned per litter, piglet survivability, litter weaning weight, and litter weight gain were in the same direction as those for feed intake and water usage in the sows, the difference in measurements of litter performance was not statistically important among treatments (P = 0.15 or greater). Intakes of DM, N, and GE by the sows were increased by 9, 4, and 7% and apparent digestibilities of DM, N, and GE were increased by 6, 5, and 7%, respectively, as particle size of corn was decreased from 1,500 to 600 μm (linear effects, P<0.001). Finally, excretion of DM and N in the feces was decreased (linear effect, P<0.002) by 178 g/d and 5 g/d, respectively, as particle size of the corn on the sow diets was reduced. In conclusion, reducing particle size of corn did not affect litter performance but increased feed intake and digestibility of nutrients and reduced nutrient excretion in sows.
Keywords: Sow; Particle Size; Lactation; Digestibility; Swine